DEVELOPING TEACHING MATERIAL OF POETRY APPRECIATION BASED ON STUDENTS’ COMPETENCY ANALYSIS - Satinem Satinem; Juwati Juwati; Noermanzah Noermanzah (University of Kuningan, 2020)
The aim of this research was to develop the material of poetry appreciation at the Department of Indonesian Language and Literature Education of STKIP PGRI Lubuklinggau. The type of this research was Research and Development (R&D) which was developed by the Dick, Carey, and Carey. Data collection was conducted through questionnaire, interviews, and tests. The data analysis and validity test were performed by using pretest and posttest of performance. The data is then processed by using a simple paired t test with the SPSS 20 program. The result of this research can be measured Asym.Sig. (2-tailed) 0,000... < 0,05. Therefore the value of t-hit 36,956 and t-tab 2,045 to (d) 17 and alpa 0,05, so it can be concluded t-hit <t-tab, so Ho has rejected, an Hi was accepted, its’ meaning that the average value of students' ability to appreciate poetry after using instructional materials as a result of development was equal to 70 or more than 70. Thus, the model of instructional materials developed has been feasible and effective for lecturers